SEGMENTASI WISATAWAN BERBASIS PENGALAMAN WISATA DI KAWASAN ATRAKSI WISATA ALAM PEGUNUNGAN JAWA BARAT - Kusumawati, Resti Aulia; Setiyorini, Heri Puspito Diyah; Khaerani, Rijal (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2025)
AbstractSegmentation is a fundamental analytical approach employed to achieve targeted marketing objectives effectively. This study focuses on analyzing tourist experiences at mountainous natural attractions. The variale used in analysing the experience derived from Customer Experience Quality (EXQ) variable, encompassing four key dimensions: Product Experience, Outcome Focus, Moments-of-Truth, and Peace-of-Mind. Employing a quantitative methodology, the research applies factor formation, followed by cluster generation using the K-Means method on data collected from 405 respondents. The result shows three distinct cluster, namely Holistic Travel, Interactive Service, and Customer Centric. These findings contribute theoretical enhancement on tourist experience and managerial implications to develop the natural based tourist attraction, in particular on the mountainous. The marketing strategy was created to prioritize roles based on tourists' choices under the name Begin From You Marketing Strategy. The strategy is systematically designed based on the results of the research with a complete description presented before-implementation-after the activity. The implementation of marketing strategies has the potential to have a positive impact, especially in the economic impact of the surrounding community.Keywords: Segmentation; Strategy; Experience; Mountain Tourism, Tourism, K-MeansAbstrakSegmentasi adalah pendekatan analitis mendasar yang digunakan untuk mencapai tujuan pemasaran yang ditargetkan secara efektif. Penelitian ini berfokus pada analisis pengalaman wisatawan pada daya tarik wisata alam pegunungan. Variabel yang digunakan dalam menganalisis pengalaman berasal dari variabel Customer Experience Quality (EXQ), yang mencakup empat dimensi utama: Product Experience, Outcome Focus, Moments-of-Truth, and Peace-of-Mind. Dengan menggunakan metodologi kuantitatif, penelitian ini menerapkan pembentukan faktor, diikuti dengan pembentukan klaster menggunakan metode K-Means pada data yang dikumpulkan dari 405 responden. Hasilnya menunjukkan tiga klaster yang berbeda, yaitu Holistic Travel, Interactive Service, dan Customer Centric. Temuan ini memberikan kontribusi peningkatan teori pada pengalaman wisatawan dan implikasi manajerial untuk mengembangkan daya tarik wisata berbasis alam, khususnya di gunung. Strategi pemasaran dibuat mengutamakan peranan berdasarkan pilihan wisatawan dengan nama Strategi Pemasaran Begin From You. Strategi dirancang secara sistematis berdasarkan hasil penelitian disertai uraian lengkap yang dipaparkan sebelum-pelaksanaan-sesudah kegiatan. Penerapan strategi pemasaran berpotensi untuk memberikan dampak positif khususnya dalam dampak ekonomi masyarakat sekitar.Kata Kunci: Segmentasi; Strategi; Pengalaman; Wisata Pegunungan; Pariwisata; K-Means